PERANAN â€œ KETUO ADATâ€ DALAM MASYARAKAT SUKU MELAYU DI KOTA BENGKULU - Sazili Sazili; Hilyati Milla (Universitas Muhammadiyah Bengkulu, 2021)
This research was aimed at findingout of the roles of Ketuo Adat of the Malay Community in Bengkulu City. It used the qualitative approach as developed by Spradley (1980). The data collected came from a number of informants consisting of ketuo adat, community leaders, and common people. The informants were selected using the snowball sampling technique. The data collection was conducted through observation, interview, and documentation study. The technique validity of the data, including the credibility, transferability, defendability, and comfimability, used triangulation. The finding show that ketuo adat had dominant and various roles in the past, Such as in leading and guiding the people, solving the customary problems, collecting the tex, leading the customary wedding ceremony, leading the funeral ceremony, and leading the shaving ceremony for a newborn baby. Moreover, ketuo adat also took care of the everyday affairs and set the social law. Nevertheless, in recent years the role of ketuo adat has been diminishing with the rapid social changes that result from educational developments, modernization, and globalization. The result of the study also indicate that several changes have occurred among te Malays in Bengkulu City. The changes are partially due to the enforcement of UU No. 5/ 1979, the effect of cultural acculturation, the effect of globlisation, and the decreasing popularity of ketuo adat. The Changes are continually reducing the people dependence on ketuo adat .Should any conflict develop among members of the community, for example, people tend to ask the governmental apparatures, such as the police and â€œlurahâ€, to settletheir dispute. They perceive that the apparratures are more legitimate than ketuo adat.